2016
DOI: 10.1080/15389588.2016.1195495
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar vertebrae fracture injury risk in finite element reconstruction of CIREN and NASS frontal motor vehicle crashes

Abstract: In conclusion, precrash positioning has a large effect on lumbar injury metrics. The lack of lumbar injury criteria in regulatory crash tests may have led to inadvertent design of seat pans that work to apply axial force to the spinal column during frontal crashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Mattos et al analyzed the damage to the head and cervical spine during a rollover [ 26 ]. Jones et al performed an analysis of lumbar spine fractures at the time of the collision [ 27 ]. Paas et al analyzed the mechanism of shoulder injury at the time of an accident [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mattos et al analyzed the damage to the head and cervical spine during a rollover [ 26 ]. Jones et al performed an analysis of lumbar spine fractures at the time of the collision [ 27 ]. Paas et al analyzed the mechanism of shoulder injury at the time of an accident [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed lumbar spine model was based on the section from the 50 th percentile Total HUman Model for Safety v6.1 (THUMS) developed by Toyota Motor Corporation, and it was used e.g. in research by (Mendoza-Vazquez et al, 2015;Jones et al, 2016). The setup of the model is shown in The normal directions of the CSs planes were calculated as an average of the normal directions of the planes created on the superior and inferior endplates of the given vertebra.…”
Section: Detailed Lumbar Spine Section Modelmentioning
confidence: 99%
“…Lumbar spine posture was also found to be an important factor affecting lumbar spine injuries. It was reported that slouched posture may cause an increase in stress on the lumbar vertebrae [ 7 ] and more reclined postures are associated with a higher lumbar vertebrae fracture risk by reconstructing real-world motor vehicle crashes [ 8 ]. Crash pulse magnitude and shape are also crucial for determining lumbar spine injury risk.…”
Section: Introductionmentioning
confidence: 99%